Cultural Genocide: Between Recognition and Denial - Fabijanić Gagro, Sandra (PRAWO i WIĘŹ, 2026)
This article explores the concept of cultural genocide, returning to its conceptual “roots” and aiming, among other things, to explore its origins as articulated by its foremost advocate, Raphael Lemkin. As the scholar who coined the term “genocide” and played a pivotal role in shaping the 1948 Genocide Convention, Lemkin’s contributions provide essential context for this analysis. During the drafting of the Convention, cultural genocide emerged as a central issue, occupying a prominent place in the debate on the nature of the crime. Despite its prominence in the discussions, it was ultimately excluded from the final text following extensive debate among the Convention’s drafters. Unlike biological and physical genocide, which were retained as the core forms of the crime, cultural genocide was excluded. What were the principal arguments advanced for and against the recognition of cultural genocide? Why does the debate over its inclusion persist decades after its exclusion from the Genocide Convention? To what extent – if at all – do these discussions hold legal significance today? These are the central issues that this article seeks to address.